The Control of Panicle Blight Bacterial Pathogen on Rice Seeds Through In Vitro Treatments - SAFNI, IRDA; UTARI, UCI; TOBING , MARYANI CYCCU; LISNAWITA (Borneo Journal of Resource Science and Technology, 2020)
Burkholderia glumae is a seed-borne pathogen of rice known to cause bacterial panicle blight disease. The lack of effective control methods makes seed treatment the alternative management approach. The aim of this research was to determine an effective seed treatments technique, using liquid smoke, clove oil, hot water and copper hydroxide fungicide treatment against bacteria B. glumae. The experiment used a complete randomized design with five treatments and three replications, including control, liquid smoke, clove oil, hot water, and copper hydroxide fungicide. The results showed the propensity for all treatments to reduce bacterial populations on rice seeds, while liquid smoke, clove oil, and fungicide did not reduce vigour and viability. Application of copper hydroxide fungicide 77% at concentration of 5% was recommended as the best treatment to control the bacterial pathogen. Keywords: Burkholderia glumae, clove oil, copper hydroxide fungicide, hot water, liquid smoke, rice